Prevalence and predictors of failure in labor induction among pregnant women delivered in Northern-Tanzania 2000-2015: A Registry-based Retrospective Cohort Study (Tanzania Medical Journal, 2019)
BackgroundThe proportion of induced deliveries is increasing steadily among referral hospitals of Tanzania. However, there is limited information regarding the failure rates of this important obstetric intervention. Factors that are associated with failure rate have also not been well documented. This information is important for practicing clinicians as it may help to understand some maternal and fetal characteristics that contribute to failure in labor induction and thereby provide women with timely alternative modes of delivery. This may reduce morbidities and mortalities related to emergency Cesarean deliveries following induction of labor. This study aimed to determine the prevalence and factors associated with failure in labor induction among women who delivered at KCMC hospital in Northern-Tanzania.MethodsA hospital-based retrospective cohort study was designed using maternally-linked data from Kilimanjaro Christian Medical Centre (KCMC) medical birth registry among women who delivered singleton babies from 2000 to 2015. All deliveries that were induced using any method were included. Failure in labor induction was defined as inability to achieve vaginal delivery after labor induction. Women with missing information on induction of labour status were excluded from analysis. Data analysis was performed using Stata version14.0. Relative risk and 95% Confidence Interval for factors associated with failed induction were estimated using Log-binomial regression models. Robust variance estimations were used to take into account for repeated deliveries from the same woman.ResultsA total of 11,483 deliveries were analyzed. The rate of failed labor induction (fIOL) was 19%. Independent predictors of fIOL include primiparity (RR = 1.83; 95% CI: 1.57 – 2.14), pre-pregnancy obesity (RR =1.58; 95% CI: 1.33-1.67), fetal macrosomia (RR = 5.30; 95% CI: 2.47 – 11.37) and rural residence (RR =1.20; 95% CI: 1.08 – 1.34).ConclusionNumerous factors were associated with fIOL. Assessment of these factors and preparation for alternative delivery mode prior an intervention is warranted to reduce adverse pregnancy outcomes related to failed labor induction.Key words: Labor Induction, Failed labor induction, Predictors, Tanzania.